Clinical and economic burden of heparin-induced thrombocytopenia in hospitalized patients undergoing percutaneous peripheral arterial interventions. (February 2020) - Subahi, Ahmed; Osman, Mohammed; Adegbala, Oluwole; Abubakar, Hossam; Kheiri, Babikir; Yassin, Ahmed S; Khalid, Mowyad; Akintoye, Emmanuel; Eljack, Ammar; Osman, Khansa; Alkhouli, Mohamad
Background: Percutaneous peripheral arterial intervention (PPAI) patients are at a high risk of developing heparin-induced thrombocytopenia due to the need for repeated and prolonged heparin exposure. We sought to investigate the incidence, outcomes, and economic impact of heparin-induced thrombocytopenia post-PPAI utilizing the National Inpatient Sample. Methods: All patients who underwent PPAI (age ≥18 years) from 2007 to 2014 were identified by using ICD-9-CM codes. Patients were then classified into two groups based on the presence or absence of heparin-induced thrombocytopenia during hospitalization. In-hospital outcomes were compared between the two groups after propensity-score matching to account for differences in baseline characteristics. Results: Heparin-induced thrombocytopenia was reported in 527 patients (0.23%). After adjusting for patient-level and hospital-level characteristics, in-hospital mortality differences were not significantly different between patients with heparin-induced thrombocytopenia vs. those without heparin-induced thrombocytopenia (odds ratio (OR) 1.02, 95% confidence interval (CI) 0.67 to 1.57, p = 0.951). However, PPAI patients with heparin-induced thrombocytopenia were more likely to develop ischemic stroke (OR 3.84, 95%CI 1.26 to 11.75, p = 0.018), deep venous thrombosis/pulmonary embolism (OR 1.32, 95%CI 0.79 to 1.79, p = 0.078), and acute kidney injury requiring dialysis (OR 4.04, 95%CI 1.72 to 9.50, p = 0.001). Furthermore, post-PPAI patients who developed heparin-induced thrombocytopenia had longer hospitalizations (13.8 vs. 9.8 days, p < 0.0001), higher cost of stay (62, 022 vs. 44, 904, p < 0.0001), and higher rates of non-routine home discharges (50.15% vs. 42.19%, p = 0.013). Conclusion: Among patients who underwent PPAI, heparin-induced thrombocytopenia was associated with a higher risk of venous thrombosis/pulmonary embolism, ischemic stroke, acute kidney injury requiring dialysis, prolonged hospital stay, and increased cost.